Fetal anterior abdominal wall thickness between gestational diabetes and normal pregnant women - Supapen Lertvutivivat; Prasert Sunsaneevithayakul; Pornpimol Ruangvutilert; Dittakarn Boriboonhirunsarn (Elsevier, 2020)
Objectives: To compare fetal anterior abdominal wall thickness (AAWT) between women with and without GDM during third trimester and to determine accuracy of AAWT to predict large for gestational age (LGA) infants. Materials and methods: A total of 250 pregnant women, including 125 women with GDM and 125 women without GDM, were enrolled. Tansabdominal ultrasonographic examinations were performed at 28-30, 32-34 and 36-38 weeks. In addition to standard fetal biometries, AAWT was measured. Patient characteristics and ultrasonographic measurements were compared between groups. Sensitivity and specificity of AAWT for identifying LGA were evaluated. Results: While standard fetal biometries were comparable, mean fetal AAWT in GDM women were significantly higher than those without GDM at 28-30 weeks (2.8 ± 0.8 vs. 2.6 ± 0.6, p = 0.006) and 32-34 weeks (4.0 ± 0.9 vs. 3.5 ± 0.8, p = 0.042). LGA infants had significantly higher fetal AAWT at each time point only in GDM women. Using cut off values of AAWT of ≥2.0, 3.0, and 4.0 mm at 28-30, 32-34, and 36-38 weeks, sensitivity for LGA diagnosis in GDM women were 94.4%, 93.9%, and 89.3%, respectively. The use of abdominal circumference (AC) at >90th percentile showed lower sensitivity but higher specificity, regardless of GDM status. Combination of both measurements increased sensitivity to approximately 90% or higher in every time point, especially among GDM women. Conclusion: Significant increase in fetal AAWT was observed in GDM women at 28-30 and 32-34 weeks. Fetal AAWT significantly increased among LGA infants and had higher sensitivity than AC in identifying LGA during third trimester. In GDM women at 28-30 weeks, AAWT ≥2.0 mm and AC >90th percentile had 97.2% sensitivity for LGA diagnosis.